Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've tried to solve the question in two different ways :

  1. Using Characteristic function(CF).

$$CF(A) = \{ 1, x \in A \text{ ; } 0, \text{elsewhere}\}$$ $$CF(B) = \{ 1, x \in B \text{ ; } 0, \text{elsewhere} \}$$ $$CF(C) = \{ 1, x \in C \text{ ; } 0, \text{elsewhere} \}$$

Since, $$A \cap C = B \cap C $$ $$CF(A) * CF(B) = CF(B) * CF (C)$$ $$\text{Therefore, } CF(A) = CF(B)$$ $$\implies A=B$$

  1. Consider the following counter example :

    Let $$A = \{1,2,3\} , B = \{2,3,4,5\} , C = \{2,3\}.$$ $$A \cap C = \{2,3\} \text{ and } B \cap C = \{2,3\} \text{ but } A \neq B.$$ Hence disproved by counter example.

Which one is correct ? Many thanks in advance.

share|improve this question
add comment

3 Answers 3

up vote 5 down vote accepted

The statement $A \cap C = B \cap C \implies A = B$ is false.

Your conclusion that "Therefore, $CF(A) = CF(B)$" is false, since you didn't consider the possibility of dividing by zero.

Your counterexample is sufficient to disprove the statement. Also, I would suggest considering three disjoint sets $A, B, C$. In this case, $A \cap C = \varnothing = B \cap C$, yet $A \neq B$

share|improve this answer
    
I'm studying this concept in school; only there's bit more to this shown here than I've learnt so far. –  David Sep 28 '11 at 2:24
    
@David: I'm not sure I get what you're trying to say. Would you like me to elaborate? –  The Chaz 2.0 Sep 28 '11 at 2:27
    
Thank you very much. Could you please elaborate how o disprove using characteristic functions i.e. by considering dividing by 0 ? –  Sunil Sep 28 '11 at 14:24
    
@Sunil How do you go from $CF(A) * CF(C) = CF(B) * CF (C)$ to Therefore $CF(A)=CF(B)$? ;) –  N. S. Oct 23 '12 at 21:21
add comment

A picture might help with this one too: enter image description here

share|improve this answer
add comment

And, of course, if $C = \varnothing$ then $A \cap C = B \cap C = \varnothing$ for any $A$ and $B$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.